If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-16x + 13) + (-20x + 23) = 180 Reorder the terms: (13 + -16x) + (-20x + 23) = 180 Remove parenthesis around (13 + -16x) 13 + -16x + (-20x + 23) = 180 Reorder the terms: 13 + -16x + (23 + -20x) = 180 Remove parenthesis around (23 + -20x) 13 + -16x + 23 + -20x = 180 Reorder the terms: 13 + 23 + -16x + -20x = 180 Combine like terms: 13 + 23 = 36 36 + -16x + -20x = 180 Combine like terms: -16x + -20x = -36x 36 + -36x = 180 Solving 36 + -36x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -36x = 180 + -36 Combine like terms: 36 + -36 = 0 0 + -36x = 180 + -36 -36x = 180 + -36 Combine like terms: 180 + -36 = 144 -36x = 144 Divide each side by '-36'. x = -4 Simplifying x = -4
| 2(2x-12)=28 | | 21+2(60)=750 | | -2(x-3)+4=2x-1 | | -5=16+x | | -14=a-39 | | 3x^3-6x^2-189=0 | | 12x+3y-9=0 | | (6x+44)+(-10x+65)=180 | | 5x^(3/2)-25x^(1/2)+30x^(-1/2) | | 35x^6/7x^(1/4) | | 11+(-6)(3)= | | 3x+9=5x+10 | | 7x-10/4=-6 | | 0=2v-8 | | 22/2+(-6)(3) | | 5295/4.13 | | 8=-w+14 | | 7x-10/4=6 | | 3x-12x=4x+7x-16 | | 3(2z-7)=5z+17+2 | | 3x+4x-6=2 | | (22x+253)/30=11 | | (X/4)=23 | | c/2+3=-2 | | 18+x=51 | | 3y^2+15y=42 | | c/2+3-3=-2-3 | | 15y-14y+5=6 | | 5x-11=9-(4-14) | | 2r^3-3r^2=32r-48 | | 4x-9=24-3 | | 3/5x-10=-1 |